Satu kajian kualitatif terhadap permasalahan pembelajaran dan pencapaian akademik pelajar anak-anak yatim muslim di Kota Tinggi, Johor - Misran, Rahayu (2012)
This study was conducted on the area of counselling with an aim to explore the learning and academic problem and the Muslim orphans in Kota Tinggi. This study employed a qualitative method with the use of a case study. Data collection involved interviews with six participation. The sampel method used is purposive sampling. The obtained data analysed by using thematic analysis. From the conversations with the six Muslim orphans it were discovered that the learning problem among them were due to their problems with peers, personal mettle and their sense of lazineess. While their academic problems were coused by the difficult to undestend the subjects and the failure to answers examation question. In addition there students perceived that the subject were difficult. In conclusion, this study provides an indepth view on the learning and academis problem among the Muslim orphans in Kota Tinggi. The researchers that this study can provide some in others to orphans hostel management, the school administration and guidance and conseling teachers and the teachers the respective subjects. It also hoped that the findings and recommendations presented serve as a guide and reference to others involved